Denarno nadomestilo med brezposelnostjo po Zakonu o urejanju trga dela - Keblič, Bernarda (Delavci in delodajalci, 2012)
The author discusses current questions of the unemployment insurance system after the adoption of the new Labour Market Regulation Act. Of all the rights an unemployment person is eligible to, the author pays special attention to the eligibilty for unemployment benefit for the duration of unemployment under the new legislation.
Keywords: brezposelnost; socialna varnost; trg dela; trg delovne sile; zavarovanje